Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2208672
|View full text |Cite
|
Sign up to set email alerts
|

Breaking news on twitter

Abstract: After the news of Osama Bin Laden's death leaked through Twitter, many people wondered if Twitter would fundamentally change the way we produce, spread, and consume news. In this paper we provide an in-depth analysis of how the news broke and spread on Twitter. We confirm the claim that Twitter broke the news first, and find evidence that Twitter had convinced a large number of its audience before mainstream media reported the news. We also discover that attention on Twitter was highly concentrated on a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 7 publications
1
82
2
1
Order By: Relevance
“…β3: Twitter users who have large followings produce a disproportionate amount of retweeted content (Hu et al, 2012;Kwak et al, 2010). Since retweets are a form of an @-mention, we include this variable to control for this effect.…”
Section: Each Of the Variables Is In Matrix Form And Is Constructed Amentioning
confidence: 99%
“…β3: Twitter users who have large followings produce a disproportionate amount of retweeted content (Hu et al, 2012;Kwak et al, 2010). Since retweets are a form of an @-mention, we include this variable to control for this effect.…”
Section: Each Of the Variables Is In Matrix Form And Is Constructed Amentioning
confidence: 99%
“…They are observed the opposition that is positive or negative impact on the campaign. Other research analyzes the news spread [11]. They looked how quickly spread the different types of news.…”
Section: Twittermentioning
confidence: 99%
“…For example, reference [6] has created one of the very first studies that looked at the topological characteristics of Twitter and its power as a new medium of information sharing and found that the dominant topics of the most active tweets (around 85%) are news headlines or information of that nature. Reference [4] examined how the news broke and spread on Twitter and concluded that Twitter was the first to break many news stories online and Twitter has a way of confirming information before the news is reported in formal media. Both studies considered analyzing tweets from massive data without specifying the context of these tweets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, news often first breaks on Twitter. For example, when the news of Osama Bin Laden's death was traced back to its first source, it was discovered that the story started with a single user who tweeted the news to his followers before it was officially published by the White House and various news channels [4]. Given the speed of tweets, which travel in certain communities, it is assumed that news related to local events has as much popularity [12].…”
Section: Introductionmentioning
confidence: 99%